RENEWING THE TRAINING MODEL FOR MANAGERS OF PUBLIC HIGHER EDUCATION INSTITUTIONS IN VIETNAM, MEETING THE REQUIREMENTS OF SELF-CONTROL, SELF-RESPONSIBILITY - Dao, Thuy Thi Thanh (Advances in Social Sciences Research Journal, 2019)
Training and retraining to enhance the capacity of the managerial staff of tertiary education institutions play a decisive role in the quality of university education and the effectiveness of university administration in the context of the need for autonomy and self-control to meet the requirements of society and international integration. Such competence is not limited to the professional standards of a teacher, but also the standardization of his political qualities, ethics and capability to lead and manage the university board. Unlike fostering professional qualifications of university lecturers in general, a unique model based on the job/position based system and a competency framework to retrain this team should be built. The article deals with the issues of program, content, methods, forms of training and retraining managers of tertiary education institutions. The proposal to renew the training model for this team in the coming time is thereby made.